2004
DOI: 10.1257/0002828041464614
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Role of Social Isolation on Stated Preferences

Abstract: Benefit-cost analysis remains the central paradigm used throughout the public sector. A necessary condition underlying efficient benefitcost analysis is an accurate estimate of the total value of the nonmarketed good or service in question. While economists have long measured the benefits of private goods routinely bought and sold in the marketplace, a much more difficult task faces the practitioner interested in estimating the total benefits of increased air and water quality, for example. In such cases, poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
111
2
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(125 citation statements)
references
References 18 publications
4
111
2
4
Order By: Relevance
“…For example, List et al (2004), Leider et al (2009), andDellaVigna et al (2011) try to measure the 'why' of sharing, and find that social pressure and incentive-based motives are important. Barr and Genicot (2008) and Attanasio et al (2009) try to understand the 'who' of sharing.…”
Section: Related Literaturementioning
confidence: 99%
“…For example, List et al (2004), Leider et al (2009), andDellaVigna et al (2011) try to measure the 'why' of sharing, and find that social pressure and incentive-based motives are important. Barr and Genicot (2008) and Attanasio et al (2009) try to understand the 'who' of sharing.…”
Section: Related Literaturementioning
confidence: 99%
“…While this ensured that members of the same group were spatially separated in the double-anonymous treatment, the additional distance itself also constitutes a difference that might have affected behavior. List et al (2004) examine whether the elicitation method affects responses in a contingent valuation exercise. 8 Respondents in the study are asked to vote "Yes" or "No" on contributing $20 to provide start-up capital for a new Center for Environmental Policy Analysis at the University of Central Florida.…”
Section: Previous Literaturementioning
confidence: 99%
“…In addition, there are two recent papers that investigate selection effects and fail to find confirming evidence for the hypothesis that students with stronger prosocial inclinations are more likely to self-select into experiments (Cleave et al, 2010;Falk et al, 2010). The effect of variations in scrutiny on other-regarding behavior has also been empirically investigated in several papers before (see, in particular, Hoffman et al, 1994;Bolton and Zwick, 1995;Laury et al, 1995;Hoffman et al, 1996;Bolton et al, 1998;List et al, 2004;Cox and Deck, 2005). However, as we will discuss in much more detail in section 2 the existing studies not only provide mixed results, but differences in experimental procedures and games within and across studies make it difficult to get a coherent overall picture of the results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 1 The term hypothetical bias is somewhat misleading because it suggests that one single real value exists with which we can compare the value obtained from a hypothetical situation. However, studies have shown that experimental situations involving real payoffs can also lead to biased estimates (e.g., Alpízar et al 2008;List et al 2004). 2 There are other suggestions for how to reduce hypothetical bias, for example, ex-post calibration of the WTP responses with follow-up questions on certainty (e.g., Champ et al 1997;Champ and Bishop 2001) and time-tothink protocols (Cook et al 2007;Whittington et al 1992).…”
Section: Introductionmentioning
confidence: 99%